Homesick : stories - Cipri, Nino (Dzanc Books, 2019)
Dark, irreverent, and truly innovative, the speculative stories in Homesick meditate on the theme of home and our estrangement from it, and what happens when the familiar suddenly shifts into the uncanny. In stories that foreground queer relationships and transgender or nonbinary characters, Cipri delivers the origin story for a superhero team comprised of murdered girls; a housecleaner discovering an impossible ocean in her least-favorite clients' house; a man haunted by keys that appear suddenly in his throat; and a team of scientists and activists discovering the remains of a long-extinct species of intelligent weasels.